The Response of Parental Time Investments to the Child's Skills and Health - Cheti Nicoletti; Valentina Tonei (Institute of Labor Economics (IZA), 2017)
Recent empirical research in family economics has shown the importance of parental investments on child's human capital development, but it is still not clear whether parents respond to changes across time in their child's skills and health. Using the Longitudinal Study of Australian Children, we measure parental investments by considering the time parents spend with their child doing formative activities. By adopting a child fixed-effect instrumental variable estimation to address endogeneity issues, we find that parents reinforce for differences in their child's socio-emotional skills, compensate for changes in her physical health, and are neutral to variation in her cognitive skills.
Keywords: J13; D13; C23; C26; 330; time-use; family investment; quality time; skills; child development